2021
DOI: 10.1007/s00330-021-08201-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary renal sarcomas: imaging features and discrimination from non-sarcoma renal tumors

Abstract: Objectives To assess imaging features of primary renal sarcomas in order to better discriminate them from non-sarcoma renal tumors. Methods Adult patients diagnosed with renal sarcomas from 1995 to 2018 were included from 11 European tertiary referral centers (Germany, Belgium, Turkey). Renal sarcomas were 1:4 compared to patients with non-sarcoma renal tumors. CT/MRI findings were assessed using 21 predefined imaging features. A random forest model was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…While renal tumors with classical radiological findings often undergo upfront surgical resection, biopsies might be benefitial in patients presenting with atypical renal tumors. For example, patients with very large, heterogeneous renal tumors and infiltration of adjacent organs have a higher probability of renal sarcoma, as reported in an earlier study, and might thus benefit from a tumor biopsy 25 .…”
Section: Discussionmentioning
confidence: 60%
“…While renal tumors with classical radiological findings often undergo upfront surgical resection, biopsies might be benefitial in patients presenting with atypical renal tumors. For example, patients with very large, heterogeneous renal tumors and infiltration of adjacent organs have a higher probability of renal sarcoma, as reported in an earlier study, and might thus benefit from a tumor biopsy 25 .…”
Section: Discussionmentioning
confidence: 60%
“…At MRI shows mixed areas of low, intermediate, and high T2 signal intensity; hypointense on T1-weighted images with areas of hemorrhage, fluid levels, and septa; small renal sarcomas can resemble skeletal muscle on T1-wigthed images [24,29,[35][36][37][38]. The main characteristics which help distinguish a renal sarcoma vs non-sarcoma mass are in truth not so specifics and are substantially the usuals traits of malignant neoplasms: right sided, larger than non-sarcoma renal tumors and has a more irregular tumor shape and margins, showing also local aggressive growth and vessels infiltration [40,41]. Uhlig et al have suggested a diagnostic radiological imaging algorithm for the prediction of the histotype of genitourinary tract sarcomas with good results, but the same authors conclude that the only specific imaging regard more fat proportion in liposarcomas versus Ewing's sarcoma and leiomyosarcoma [40].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced imaging techniques, such as CT and MRI, provide a wealth of information otherwise impossible by traditional 2D histopathology. It is prudent to note here that the complex datasets delivered by such advanced imaging modalities also need thorough analysis, and that is where a radiomics-based machine learning approach holds its major advantages 26 .…”
Section: Discussionmentioning
confidence: 99%